(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Because the prevalence of ocular trauma in Ukraine remains high, restorative and reconstructive surgeries in the orbit, adnexa, and periorbital area are important; their success, however, depends on the quality of implant materials. Previously, we have developed a polymer material made of cross-linked polyurethane (PU) and containing a biologically active substance, albucid; it seems to be a promising implant material. Purpose: To assess in vitro cytotoxicity and pH of extracts of synthetic polymers made of cross-linked PU composites containing and not containing albucid. Material and Methods: Cell culture methodology was applied to assess in vitro cytotoxicity of cross-linked PU composites containing and not containing albucid. Subcutaneous adipose tissue of albino Wistar rats was used as a source of cells to induce growth of fibroblasts and fibroblast-like cells under culture conditions. The pH value of water solutions was determined through the study of extracts of samples of PU composites containing and not containing albucid. The extracts were examined for pH using the general-purpose pH meter EV-74 supplied with glass pH electrodes. Conclusion: It was demonstrated that fibroblast culture in Carrel flasks with controls as well as in those with extracts of samples of PU composites containing and not containing albucid was in a stable growth phase, indicating no toxic effect of the extracts on cultured cells. Polyurethane composites containing albucid were found to have a neutral pH value, which was within the acceptable range defined by hygiene standards.